Pengusahaan Penambangan Minyak Bumi Pada Sumur Tua Oleh Masyarakat Kecamatan Kedewan Kabupaten Bojonegoro - Kushariyadi; Gilang Muhammad Rido; Tri Warcono Adi; Nabila Andari; Savira Putri Faiza (Syntax Idea)
To optimize national oil production and improve the quality of life and welfare of the community, it is deemed necessary to issue regulations on the management and operation of old oil wells scattered in mature oil fields. In line with this, the Government, represented by the Ministry of Mining and Energy, issued Ministerial Decision No. 1285K/30/MPE/1996, later revised by Ministerial Regulation No. 01 of 2008 concerning Guidelines for the Operation of Oil Mining in Old Wells. This can be interpreted as the embodiment of the meaning contained in Article 33 of the 1945 Constitution, providing a breath of fresh air for Local Governments with numerous old wells. The said regulation offers a path and hope for the increase in the Regional Budget (APBD) and the welfare of the people through the participation of cooperatives (KUD) or Regional-Owned Enterprises (BUMD) in oil production from old wells within their jurisdiction. Kedewan District, Bojonegoro Regency, is one of the regions in East Java Province that is an active oil and gas-producing area to date. The oil fields in Kedewan District, Bojonegoro Regency, consist of old oil wells that have been in production since the Dutch colonial era, resulting in suboptimal production. The potential of these old oil wells can still be managed and utilized through traditional mining methods involving the local community. The most prominent and successful operation of old oil wells in the working area of PT Pertamina EP Asset 4 Cepu Field, especially in the villages of Kedewan District, Bojonegoro Regency, utilizes simple technology with a bucket method, making it relatively more economical.